2022
DOI: 10.3390/ijerph192214848
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Intergovernmental Cooperation on Emission Reduction in Chengdu-Chongqing Urban Agglomeration: An Evolutionary Game Theory Perspective

Abstract: In this study, we introduced the realistic problem of a dynamic carbon tax, built several evolutionary game models for cooperative emission reduction by local governments, and determined the factors that influence governments’ willingness to cooperate in emission reduction. The findings revealed that, first, the probability of governments opting for cooperative emission reduction strategies increases at different rates depending on the benefits and costs of cooperation. Second, externalities influence governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…With the strengthening of government supervision, leading companies with a smooth transformation and low-carbon technology have strengthened their market leadership, while companies without low-carbon technology have adapted to the market or exited the market under carbon emission constraints, and the industrial structure has gradually transformed from a decentralized competitive structure to a centralized oligopolistic structure [40]. To better achieve inter-regional carbon emission reduction, the central government and local governments should take cooperative actions [41].…”
Section: The Application Of Evolutionary Games For Carbon Emission Re...mentioning
confidence: 99%
“…With the strengthening of government supervision, leading companies with a smooth transformation and low-carbon technology have strengthened their market leadership, while companies without low-carbon technology have adapted to the market or exited the market under carbon emission constraints, and the industrial structure has gradually transformed from a decentralized competitive structure to a centralized oligopolistic structure [40]. To better achieve inter-regional carbon emission reduction, the central government and local governments should take cooperative actions [41].…”
Section: The Application Of Evolutionary Games For Carbon Emission Re...mentioning
confidence: 99%
“…When choosing high-carbon treatment, the disposal cost is C w2 . In addition, when PMs choose low-carbon production, the treatment cost of WWTPs will be reduced due to the decarbonization of the pharmaceutical manufacturing process (Liu et al, 2022). It is a free-rider effect.…”
Section: Figure 10mentioning
confidence: 99%
“…As in the YRMRUA, more than 5% of the spatial expansion intensity is concentrated around core cities. Previous research has demonstrated that urban agglomerations encounter numerous conflicts during the construction and management phases [47], which always affect the size and capacity of urban agglomerations [48]. Additionally, the full potential of multi-poles can only be realized with a stronger population base and infrastructure in place [49].…”
Section: Spatial Solidification By Building a Tri-pole Structurementioning
confidence: 99%